Sporočanje slabe novice - Lunder, Urška (Medicinski razgledi, 2003)
Breaking bad news is one of the most difficult challenges in doctor-patient communication. It is very important, however, to both the quality of the patient's life and the future connection between doctor and patient, as well as to the patinet's complicance with treatment. Bad news is, after all, simplyinformation on the patient's health, which is communicated to the patient or his/her relatives. The conten, or the circumstances of its delivery, can have an unfavorable impact on the person receiving it, and/or may unfavorably influence the patient's ability to cope with the physical, psychological, social, work-related, family and other intangible changes it entails. Breaking bad news is a step-by-step process tailored to the patient'sneeds. In the first place, the doctor or nurse has to find out what the patient already knows, wheter he/she wants to hear the information, and, if so, to what extent. Next, the information is conveyed using suitable methods and skills, and support is provided to the patient taking into accounthis/her reactions and concerns about the bad news. Finally, future startegies for coping with the situation are developed in tandem with the patient. The skill of breaking bad news can be learned. In teaching communication skills that support the patient and do not shock him/her adversely, experiential methods of teaching have to be used. Such methods include observation (indirect observation of videotaped consultations, direct observation), role playing, practice using simulated patients, analysis of videotaped consultations, feedback after role playing and discussions about actual consultation.
Keywords: Zdravnik-bolnik odnosi; Zaupnost; medicinska etika; bolniki; zdravniki